Bioefficacy of Cymoxanil and Mancozeb against downy mildew of cucumber (Cucumis sativus) caused by Pseudoperonospora cubensis - GANESHAN, GIRIJA; CHETHANA, B S (The Indian Journal of Agricultural Sciences, 2012)
Cymoxanil (8%)+Mancozeb (64%) 72WP , a combination product of systemic and contact fungicide, was evaluated against downy mildew disease of cucumber caused by Pseudoperonospora cubensis(Berk. and Curt.) (Rostov.). Cymoxanil 50 WP and Cymoxanil (8%)+Mancozeb (64 %) 72WP at all concentrations, were found significantly effective in reducing the disease and in increasing the yield as compared to untreated control in both the years. The results of the pooled data analysis indicated that Cymoxanil (8%)+Mancozeb (64 %) 72 WP @1080 g ai/ha was significant and recorded a PDI of 22.02 and an highest yield of 12.49 tonnes/ha as against a PDI of 33.59 and yield 9.97tonnes/ha in untreated control. Since the price of the combined product is more, the cost benefit ratio was found highest in their individual components. The highest cost: benefit ratio was recorded in Mancozeb 75 WP1500 g ai/ha (1:10.45), followed by Cymoxanil 50WP 120g ai/ha (1:9.66). Thus, among the evaluated fungicides, Mancozeb 75 WP 1500g ai/ha and Cymoxanil50 WP 120g ai/ha applied at weekly interval recorded the highest cost :benefit ratio of 1:10.45 and 1:9.66 respectively.